2014
DOI: 10.1002/jsfa.6863
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of enzymatically prepared sugar medium‐chain fatty acid monoesters

Abstract: Generally, the length of fatty acid chain (hydrophobic group) and sugar groups (hydrophilic group) for sugar medium-chain fatty acid monoesters both affected the surface properties and antimicrobial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…The aqueous solution of surfactant shows a better stability of emulsion at 1 % surfactants concentration. The disaccharide fatty acid esters showed better emulsifying properties due to the presence of a long carbon chain [24,25].…”
Section: Surfactant Properties Of Sucrose Erucatementioning
confidence: 99%
“…The aqueous solution of surfactant shows a better stability of emulsion at 1 % surfactants concentration. The disaccharide fatty acid esters showed better emulsifying properties due to the presence of a long carbon chain [24,25].…”
Section: Surfactant Properties Of Sucrose Erucatementioning
confidence: 99%
“…Commercial sucrose esters are used mostly in Japan in canned beverages to provide sterilization‐stable emulsions and to inhibit the germination of spore‐forming bacterium . In recent years, sugar fatty acid esters have attracted much attention because of their biological activities, including insecticidal, antitumor, and anti‐microbial properties . Some studies reported antibacterial activity of sugar fatty acid esters to inhibit Gram‐negative bacteria, while others reported that they inhibited only Gram‐positive bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…Sugar fatty acid esters are non‐ionic biosurfactants with intriguing features such as nontoxicity, biocompatibility, non‐irritancy, and biodegradability . They are usually produced from naturally renewable resources with a number of excellent surface properties including emulsification, dispersion, solubilization, and foaming and wetting functions for applications in oil recycling, hydrocarbon bioremediation, and in the food, cosmetic, pharmaceutical, and detergent industries …”
Section: Introductionmentioning
confidence: 99%
“…1 They are usually produced from naturally renewable resources with a number of excellent surface properties including emulsification, dispersion, solubilization, and foaming and wetting functions for applications in oil recycling, hydrocarbon bioremediation, and in the food, cosmetic, pharmaceutical, and detergent industries. 2 The conventional methods of biosurfactant production include liquid fermentation/extraction from microorganisms, chemical synthesis, and enzymatic synthesis. Compared to other methods, enzymatic synthesis has the advantages of simple operation, mild reaction conditions, high catalytic activity and regioselectivity, easy separation, and reuse of the immobilized enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation